2016
DOI: 10.1016/j.immuni.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Coinhibitory Pathways in the B7-CD28 Ligand-Receptor Family

Abstract: Immune responses need to be controlled for optimal protective immunity and tolerance. Coinhibitory pathways in the B7-CD28 family provide critical inhibitory signals that regulate immune homeostasis and defense, and protect tissue integrity. These coinhibitory signals limit the strength and duration of immune responses, thereby curbing immune-mediated tissue damage, regulating resolution of inflammation, and maintaining tolerance to prevent autoimmunity. Tumors and microbes that cause chronic infections can ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
441
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 489 publications
(453 citation statements)
references
References 211 publications
(266 reference statements)
6
441
0
6
Order By: Relevance
“…18,19 However, the gene wide alterations of B7 and TNFR families remain largely unknown in colorectal cancer (CRC). Here, the frequency of B7 and TNFR gene alterations (including mutations, amplifications, and deletions) across 6 studies in colorectal cancer were shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…18,19 However, the gene wide alterations of B7 and TNFR families remain largely unknown in colorectal cancer (CRC). Here, the frequency of B7 and TNFR gene alterations (including mutations, amplifications, and deletions) across 6 studies in colorectal cancer were shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Presently, the co-stimulation pathways mainly involve two major families: the B7 family of immunoglobulins3 and the tumor necrosis factor receptor (TNFR) superfamily. 18,19 The B7 family has 10 reported members, including CD80 (B7-1), CD86 (B7-2), PD-L1 (B7-H1), B7-H2, B7-H3, B7-DC, B7-H4, B7-H5, B7-H6 and B7-H7. 18 These proteins have been proven to regulate both T cell co-stimulatory and co-inhibitory pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ligands of B7 protein family are usually expressed by antigen presenting cells and modulate T-lymphocyte activities. This family includes three subgroups: i) B7-1, B7-2, and ICOS-L; ii) Programmed Death Ligand 1 (PD-L1) and 2 (PD-L2); iii) B7-H3, B7x, and HERV-H LTR-associating 2 (HHLA2) [85,86]. Osteosarcoma cells express several members of the B7 family to escape to the immune cells.…”
Section: Lymphocytes Subpopulations In Osteosarcoma and Therapeutic Imentioning
confidence: 99%
“…Two well-studied checkpoint receptors on T-cell surfaces are CTLA-4 and PD-1, for which clinically approved inhibitors are now available. 1,2 CTLA-4 and PD-1 can bind to CD80/CD86 and PD-L1/L2, respectively, to counteract activation signals initiated by the T-cell receptor (TCR). Blocking immune checkpoints with “checkpoint inhibitor” therapy was shown to be a powerful approach to release T cell inhibition in preclinical models and is now approved by the FDA for the treatment of certain cancers.…”
Section: Introductionmentioning
confidence: 99%